Organ-Specific Immune-Related Adverse Events Associated With Immune Checkpoint Inhibitor Monotherapy Versus Combination Therapy in Cancer: A Meta-Analysis of Randomized Controlled Trials - Da, Lijun; Teng, Yuanjun; Wang, Na; Zaguirre, Karen; Liu, Yating; Qi, Yali; Song, Feixue (Frontiers in Pharmacology, 2020)
Background: Although combination therapy with immune checkpoint inhibitor (ICI) provides a promising efficacy in multiple cancers, its use is facing challenges for a high incidence of adverse effects. This meta-analysis was conducted to compare the risks of organ-specific immune-related adverse events (IRAEs) associated with ICI monotherapy versus combination therapy among cancer patients. Methods: Electronic databases were systematically searched to include eligible randomized controlled trials (RCTs). Any-grade and 3-5 grade IRAEs (colitis, pneumonitis, hepatitis, hypothyroidism, hyperthyroidism, and hypophysitis) were extracted for meta-analysis. Two reviewers independently assessed the methodological quality. The RevMan 5.3.5 software was used for meta-analysis. Results: A total of 10 studies involving 8 RCTs with 2716 patients were included in this study. The most common any-grade adverse event was colitis (14.5%), followed by hypothyroidism (13.8%), hepatitis (10.4%), hypophysitis (10.0%), hyperthyroidism (9.3%), and pneumonitis (4.6%). Meta-analysis showed that ICI combination therapy significantly increased the risks of any-grade IRAEs in colitis[RR = 3.56, 95%CI (1.56, 8.12); p＜ 0.05], pneumonitis[RR = 2.31, 95%CI (1.54, 3.45); p＜ 0.05], hepatitis [RR = 2.54, 95%CI (1.65, 3.91); p＜ 0.05], hypothyroidism [RR = 2.17, 95%CI (1.71, 2.76); p＜ 0.05], hyperthyroidism [RR = 3.13, 95%CI (2.08, 4.70); p ＜ 0.05] and hypophysitis [RR = 3.54, 95%CI (2.07, 6.07); p＜ 0.05] compared with ICI monotherapy, as well as 3-5 grade IRAEs in colitis [RR = 2.50, 95%CI (1.62, 3.86); p＜ 0.05], pneumonitis [RR = 1.99, 95%CI (1.00, 3.93); p = 0.05] and hepatitis [RR = 2.70, 95%CI (1.29, 5.63); p＜ 0.05]. Conclusions: This meta-analysis demonstrated that, compared with ICI monotherapy, patients receiving ICI combination therapy significantly increased organ-specific IRAEs in colitis, hypothyroidism, hepatitis, hypophysitis, hyperthyroidism, and pneumonitis. The incidence and severity of organ-specific IRAEs were drug and dose independent.